Diminished fitness in an endemic Hawaiian snail in nonnative host plants. Issue 3 (4th May 2017) - Holland, Brenden S.; Chiaverano, Luciano M.; Howard, Cierra K.
Abstract : Hawaii's diverse achatinellid tree snails occur almost exclusively in host trees and shrubs that are native to the Hawaiian Archipelago. A few exceptions to this pattern are known, where an arboreal gastropod population has persisted in introduced plants. On Oahu, Hawaii, the last known population of the single-island endemic snail Auriculella diaphana has persisted in nonnative plants for multiple decades, leading to the following question: are there differences in the relative fitness of native gastropods in native versus nonnative host plants? To address this we conducted laboratory trials with A. diaphana in three treatment groups, one with the two dominant nonnative host plants from their current distribution, another group with two primary native host plant species, and a third treatment maintained in cages with a mixture of equal parts of both the nonnative and native plants. Trials were replicated in two 16-week intervals, with 100 snails. Relative fitness was assessed among treatments as survival and reproductive output (number of eggs produced). Results demonstrated that while survival of adult snails was equivalent across treatments (100%), fecundity was significantly higher in cages where native plants were available. Egg production was 20.05-fold and 14.95-fold greater in treatments with 100% and 50% native host plants, respectively, than in treatments with nonnative plants only. These results suggest that native snails persisting in nonnative host plants experience sublethal stress, reflected in a dramatic reduction in reproductive output. Snails in treatments with mixed native and nonnative plants also showed significantly higher reproduction than those in nonnative plant cages. We suggest that the observed decreased fecundity was due to the poor nutritional value of the microbial phyllosphere of nonnative vegetation, and that translocation of this and related species occurring in nonnative habitat to nearby native host plants will be beneficial in terms of relative fitness.